Zjawisko elity i teorie elit w polskiej myśli socjologicznej (wybrane przykłady) = Phenomenon of the elite and elite theory in polish sociological thought - some examples - Żyromski, Marek (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The text deals with the development of the reflection on social elites in Polish sociology. The first Polish political elite theorist was a sociologist, Czesław Znamierowski, who was followed by many other sociologists, historians and political scientists. Nevertheless, most of the empirical research on the Polish political elite was done only after the fall of Communism. The author suggest that, despite the extensive research of political elites, contemporary Polish sociology shows only a marginal interest in elite theory or in non-political elites.
Keywords: elita; socjologia